Microbial biotransformation to obtain stilbene methylglucoside with GPR119 agonistic activity - Peng, Yu; Huan, Yi; Chen, Jing-Jing; Chen, Tian-Jiao; Lei, Lei; Yang, Jin-Ling; Shen, Zhu-Fang; Gong, Ting; Zhu, Ping (Frontiers in Microbiology, 2023)
Introduction Limitation of pharmaceutical application of resveratrol (RSV) and piceatannol (PIC) continue to exist, there is a need to obtain the superior analogs of two stilbenes with promoted activity, stability, and bioavailability. Microbial transformation has been suggested as a common and efficient strategy to solve the above problems. Methods In this study, Beauveria bassiana was selected to transform RSV and PIC. LC-MS and NMR spectroscopies were used to analyze the transformed products and identify their structures. The biological activities of these metabolites were evaluated in vitro with GPR119 agonist and insulin secretion assays. Single factor tests were employed to optimize the biotransformation condition. Results Three new methylglucosylated derivatives of PIC (1–3) and two known RSV methylglucosides (4 and 5) were isolated and characterized from the fermentation broth. Among them, 1 not only showed moderate GPR119 agonistic activity with 65.9%, but also promoted insulin secretion level significantly (12.94 ng/mg protein/hour) at 1 μM. After optimization of fermentation conditions, the yield of 1 reached 45.53%, which was increased by 4.2-fold compared with the control. Discussion Our work presents that 3-O-MG PIC (1), obtained by microbial transformation, is an effective and safer ligand targeting GPR119, which lays a foundation for the anti-diabetic drug design in the future.